Spatial distribution of nutrients to determine soil fertility in mixed farming based on geostatistical Kriging - Katili, Hidayat Arismunandar; Sariani, Sariani; Ongky, Ongky (Journal of Degraded and Mining Lands Management, 2025)
Soil fertility maps are vital tools in agriculture and land management, offering essential information for decision-makers. The availability of soil nutrients significantly impacts crop production. This study aimed to assess soil nutrient content and develop a soil fertility map for mixed farmland in the Banggai Islands region of Central Sulawesi, Indonesia. The research involved soil sampling at a depth of 0-20 cm from 60 random points, followed by laboratory analysis and geostatistical interpolation using the Kriging Semivariogram (Spherical) method in ArcGIS to create the soil fertility status map. Validation was conducted using absolute mean error (AME) and absolute error of variation (AVE). Results indicated that soil pH in the area ranged from slightly acidic to neutral, while organic C, nitrogen, and cation exchange capacity were evenly distributed but classified as low to medium fertility. Potassium levels were consistently low across the study area. Additionally, available phosphorus varied from low to very high, and base saturation was predominantly high to very high. By overlaying the nutrient distribution maps, three soil fertility categories, very low, low, and medium, were identified. These findings offer valuable insights into nutrient management and sustainable agricultural practices in the Banggai Islands, Central Sulawesi.